Two new species of Yangisunda Zhang (Hemiptera: Cicadellidae: Typhlocybinae: Zyginellini) from China, with a key to species - Zhang, Yalin; Gao, Xia; Huang, Min (Zootaxa, 2011)
Species of the genus Yangisunda Zhang from China are reviewed and two new species, Yangisunda apicibicruris and Y. bisbifudusa spp. nov. are described and illustrated. A key to seven species of Yangisunda is provided along with a species checklist.